Contribution of Science and Technology to the Country’s National Security - Shrestha, Chirag Govinda (Unity Journal, 2024)
In the face of Nepal's constant vulnerability to major geopolitical forces, the country has yet to fully harness technology to safeguard its national interests. This paper highlights how states, in demanding times, have wielded scientific technology to safeguard their security and address their interests. This paper draws attention to the importance of investment in innovation and research for the survival of a nation. Drawing upon historical, technological, and geopolitical perspectives, this paper explores the pivotal role of scientific and technological breakthroughs in shaping military strategies, and war efforts. The paper examines key moments when innovations such as the development of bow and arrow, gunpowder, RADAR, proximity fuse, cryptography, and computer malware have provided nations, civilizations, and communities with a vital advantage in safeguarding their security. Furthermore, the paper explores the mutual relationship between scientific research, innovation, and economic growth. It highlights how investments in science bolster a country's defence capabilities and foster innovative ecosystems that drive economic prosperity. Ultimately, this paper seeks to provide a comprehensive overview of the contributions of science to national security and well-being. Analyzing the relationship between innovation, strategy, and global dynamics; the paper highlights the imperativeness of nations to adapt, collaborate, and harness scientific advancements, to safeguard their interests in an increasingly complex world. Through an enriched understanding of the past and present contributions of science in national defence, Nepalese policymakers, military leadership, and the country’s scientific community can navigate the intricate landscape of national safe guardianship to ensure a secure and prosperous future for Nepal.